2021
DOI: 10.3390/nu13124351
|View full text |Cite
|
Sign up to set email alerts
|

Organic Food in the Diet of Residents of the Visegrad Group (V4) Countries—Reasons for and Barriers to Its Purchasing

Abstract: This study aimed to determine the differences in the frequency of, reasons for, and barriers to purchasing organic food among the inhabitants of the Visegrád Group member states. The selection of the countries for the study was dictated by the fact that the countries of Central and Eastern Europe play the role of a niche market in the European organic food market. This research employed the method of a diagnostic survey and the discriminant function. A chi-squared test, ANOVA, and Fisher’s Post Hoc LSD test we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…Siegrist and Hartmann (2020) showed in their study that cultural issues are related to the acceptance of various risks. In that direction, Soroka et al (2021) demonstrated that consumer's attitude is different from country to country in the European market. A bulk of studies on GMFs found that Asian consumers were unsure about how to use GMFs because there were only a few studies about them (Siegrist and Hartmann, 2020;Fozouni Ardekani et al, 2021).…”
Section: Theoretical Background Of Gmfsmentioning
confidence: 99%
“…Siegrist and Hartmann (2020) showed in their study that cultural issues are related to the acceptance of various risks. In that direction, Soroka et al (2021) demonstrated that consumer's attitude is different from country to country in the European market. A bulk of studies on GMFs found that Asian consumers were unsure about how to use GMFs because there were only a few studies about them (Siegrist and Hartmann, 2020;Fozouni Ardekani et al, 2021).…”
Section: Theoretical Background Of Gmfsmentioning
confidence: 99%
“…Specific rules and limitations have also been established for organic food processing [6]. There is a growing number of consumers searching for high quality foods produced with natural substances and processes [7], and thus the demand for organic products is dynamically increasing all over the world. The EU is one of the most important markets for organic foods globally [8], with organic retail sales amounting to EUR 46.7 billion in 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers buy organic foods because they associate this kind of food with a healthy and sustainable diet and lifestyle [ 10 , 11 , 12 , 13 ]. Global sales of organic products have increased significantly in the 21st century.…”
Section: Introductionmentioning
confidence: 99%